Interactions in an Acoustic World: Dumb Hole - Ion Simaciu; Gheorghe Dumitrescu; Zoltan Borsos; Mariana Brădac (Advances in High Energy Physics)
The present paper aims to complete an earlier paper where the acoustic world was introduced. This is accomplished by analyzing the interactions which occur between the inhomogeneities of the acoustic medium, which are induced by the acoustic vibrations travelling in the medium. When a wave packet travels in a medium, the medium becomes inhomogeneous. The spherical wave packet behaves like an acoustic spherical lens for the acoustic plane waves. According to the principle of causality, there is an interaction between the wave and plane wave packet. In specific conditions, the wave packet behaves as an acoustic black hole.